Are winter rangelands enough to satisfy the nutritional requirements of late‑gestation transhumant goats in Patagonia? - Caballero, Veronica Jorgelina (2022)
Transhumant herds graze across two different rangeland types according to the season. Winter rangelands differ from summer rangelands in the amount and quality of available fodder, with the former being the less productive. In cold areas, winter rangeland has low forage quality where goats may suffer severe nutritional restrictions during gestation which lead to significant reproductive losses in the form of abortions and perinatal losses. In Argentinian northern Patagonia, the transhumant Criollo goat is a dual-purpose breed, producing both meat and cashmere and grazing on winter rangelands where they complete their reproductive cycle. Our objective was to evaluate to what extent the winter rangelands of northern Argentine Patagonia satisfy the nutritional requirements needed by Criollo transhumant goats during late gestating. We evaluated a study between 2010 and 2012 where we analysed the body weight and body condition score of the goats reaching the winter rangelands and before kidding. We also analysed the botanical composition of their diet, the quality forage (metabolizable energy, crude protein and digestibility) contribution offered by the species and the proportions of the nutritional requirements of the goats during the last third of gestation. Significantly, we found a decrease in body weight and body condition score in late gestation. In 2010, the goats’ diet showed a nutritional deficiency value of 0.6 Mcal/day metabolizable energy and 30.43 g/day crude protein; in 2011, a deficiency of 0.77 Mcal/day metabolizable energy and 65.48 g/day crude protein; and in 2012, a deficiency of 0.75 Mcal/day metabolizable energy and 55.41 g/day crude protein. Forage present 51, 52 and 48% digestibility in each year, respectively. We conclude that forage quality in winter rangelands in Argentinean Patagonia is not high enough to satisfy the nutritional requirements of Criollo transhumant goats during the last third of gestation. We recommend 550 g/day of an 80:20 mixture of corn:soy expeller supplementation during late gestation.